Nalmefene vs. dexmedetomidine for prevention of postoperative hyperalgesia in patients undergoing laparoscopic gynecological surgery with remifentanil infusion: A randomized double-blind controlled trial - Jia, Zhen; Chen, Yi; Gao, Tianyu; Yuan, Yuan; Zheng, Yuxin; Xie, Yegong; Wang, Guolin; Yu, Yonghao; Zhang, Linlin (Frontiers in Pharmacology, 2023)
Intraoperative remifentanil infusion may paradoxically induce post-surgical hyperalgesia. Dexmedetomidine reportedly reduces opioid-induced hyperalgesia. Nalmefene selectively reverses several side-effects of opioids without impairing analgesia. Herein, this randomized, double-blind controlled trial investigated whether nalmefene, dexmedetomidine, and both drugs combined prevent remifentanil-induced hyperalgesia. One hundred and fifty patients undergoing elective laparoscopic gynecological surgery under desflurane anesthesia randomly received either intraoperative sufentanil 0.20 μg·kg−1 (Group S), or remifentanil 0.20 μg·kg−1 min−1 (Group R), or remifentanil and pre-anesthesia nalmefene 0.20 μg·kg−1 (Group N), or remifentanil and pre-anesthesia dexmedetomidine 0.50 μg·kg−1 (Group D), or remifentanil and the combination of dexmedetomidine 0.25 μg·kg−1 and nalmefene 0.10 μg·kg−1 (Group DN). The threshold of postoperative mechanical hyperalgesia (primary outcome) was measured with von Frey filaments. We also recorded pain intensity, analgesic consumptions, hyperalgesic area, and side-effects for 24 hours postoperatively. Compared with Group S, remifentanil reduced hyperalgesic threshold on the forearm [mean 89.4 (SD 13.7) vs. 62.2 (10.7) g, P < 0.001] at postoperative 24 hours. Pain threshold on the forearm at postoperative 24 hours was significantly lower in Group R than in Groups N, D and DN [62.2 (10.7) vs. 71.1 (12.3), 72.4 (12.9) and 78.0 (13.8) g]. Compared with Group R, Postoperative pain intensity, analgesic consumption and hyperalgesic area were lower likewise in Groups D and DN. However, the incidence of intraoperative bradycardia was lower and post-anesthesia recovery time was shorter in Group DN than Group D. Preoperative therapy of dexmedetomidine and nalmefene combined attenuates postoperative hyperalgesia in patients undergoing laparoscopic gynecological surgery under desflurane-remifentanil anesthesia.